Stability of Generalized Quartic Functional Equation in Random Normed Spaces - Devi, Sushma (Communications in Mathematics and Applications, 2023)
Aim of this paper is to investigate the Hyers-Ulam stability of generalized quartic functional equation\begin{align*}\sum^n_{i=1}\emptyset \bigg(-v_i+\sum^n_{j=1,i eq j}{v_j}\bigg)&=(n-8)\sum_{1=i
Keywords: Quartic functional equation; Hyers- Ulam stability; Random normed space